2015
DOI: 10.1111/ajt.13041
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Kidney Transplant Recipients After 20 Years of Graft Function

Abstract: There is a growing population of kidney transplant recipients who have survived 20 years with a functioning graft. This study identified the factors associated with prolonged survival and described the clinical course of recipients after two decades of transplant function. All recipients transplanted in Northern Ireland between 1968 and 1993 were included (n = 706) and data were collected prospectively. At 20 years, 25% had a functioning transplant; in multivariate analysis younger recipient age and living don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 25 publications
1
40
0
2
Order By: Relevance
“…In a study from Northern Ireland, of the 706 KTRs transplanted between 1968 and 1993, 117 (16%) were still alive with a functional graft 20 years post transplantation [20]. The authors concluded that in these long-term kidney graft survivals, the focus of management should be on the prevention of cancers and CVD, as the prevalence was very high in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Northern Ireland, of the 706 KTRs transplanted between 1968 and 1993, 117 (16%) were still alive with a functional graft 20 years post transplantation [20]. The authors concluded that in these long-term kidney graft survivals, the focus of management should be on the prevention of cancers and CVD, as the prevalence was very high in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Living donor kidney transplantation (LDKT) provides the greatest opportunity to maximize long-term patient and graft survival (1–4). Although multiple factors contribute to prolonged graft survival for LDKT recipients, human leukocyte antigen (HLA) matching remains a very impactful determinant of long-term outcome (58).…”
Section: Introductionmentioning
confidence: 99%
“…Living donor (LD) kidney transplantation provides the greatest opportunity to maximize long-term patient and graft survival. [1][2][3][4] Although multiple factors contribute to prolonged graft survival for LDKT recipients, HLA matching remains an important determinant of long-term outcome. [5][6][7][8] First-degree genetic relatives (ie, siblings, parents, offspring), therefore, represent a prevalent and accessible pool of wellmatched kidneys 1,9 that may optimize long-term allograft outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Success rates in patient management and graft survival following kidney transplantation are greater now than ever before; however, graft and patient survival is compromised following the diarrheal infection. Although NVDI appears to be less deleterious on patient and graft outcomes than infection with Clostridioides difficile , it does appear to be associated with a reduction in graft survival.…”
Section: Discussionmentioning
confidence: 99%